1998
DOI: 10.1152/jappl.1998.85.4.1337
|View full text |Cite
|
Sign up to set email alerts
|

Fiber type and citrate synthase activity in the human gastrocnemius and vastus lateralis with aging

Abstract: The purpose of this study was to determine whether enzymatic and histochemical characteristics of human skeletal muscle are altered with aging. Tissues from the vastus lateralis (VL) and gastrocnemius were analyzed for citrate synthase (CS) activity and fiber type in 55 sedentary men (age range 18-80 yr). In this population, CS activity in the gastrocnemius was negatively related to age (r = -0. 32, P < 0.05); there was no relationship in the VL. Treadmill-determined maximal oxygen consumption was positively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 27 publications
4
106
3
Order By: Relevance
“…One reason for these unexpected results may be the fact that aging-related loss of muscle fibers is associated with a selective atrophy of type 2 (mainly glycolytic) muscle fibers, resulting in higher relative amount of type 1 (oxidative) fibers in aged muscle (Thompson, 1994;Lexell, 1995). Hence aging-related changes in skeletal muscle, especially ones in relation to oxidative capacity, are controversially reported in the literature (Houmard et al, 1998). It may be speculated that the shift in fiber-type ratio is also affecting our results.…”
Section: Discussionmentioning
confidence: 71%
“…One reason for these unexpected results may be the fact that aging-related loss of muscle fibers is associated with a selective atrophy of type 2 (mainly glycolytic) muscle fibers, resulting in higher relative amount of type 1 (oxidative) fibers in aged muscle (Thompson, 1994;Lexell, 1995). Hence aging-related changes in skeletal muscle, especially ones in relation to oxidative capacity, are controversially reported in the literature (Houmard et al, 1998). It may be speculated that the shift in fiber-type ratio is also affecting our results.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast with studies of the TA, other studies have shown age-related declines in oxidative capacity of the plantarflexor muscles using both in vivo (McCully et al 1991) and in vitro approaches (e.g., enzyme activities; Coggan et al 1992;Houmard et al 1998). In the quadriceps muscles, which are most commonly studied, in vivo (Conley et al 2000;Larsen et al 2012b) and in vitro (Short et al 2005) oxidative capacities are both lower in O adults.…”
Section: Introductionmentioning
confidence: 85%
“…Differences between younger and older people in the magnitude of response in peripheral insulin sensitivity to exercise training may be explained in part by aging-related loss of muscle mass and decrements in a number of key factors related to muscle oxidative capacity in older people (6,15,23,28). Recently, Short et al (35) reported moderate-intensity (70% maximum HR), training-related improvements in insulin sensitivity that were inversely related to age, improving by 72% (P Ͻ 0.001) among younger (20 -39 yr) subjects and by 20% (P ϭ not significant) among middle-aged (40 -59 yr) subjects, but decreasing by 5% (P ϭ not significant) among people aged 60 yr or older.…”
Section: Discussionmentioning
confidence: 99%